Final report : SIM comparison in mass standards SIM.M.M-K5 - Becerra, L. O. (2016)
This report summarizes the results of a SIM comparison in masss carried out between 7 NMIs. Five mass standards with nominal values 2 kg, 200 g, 50 g, 1 g and 200 mg have been circulated by the NMIs. The results reported by the participants are consistent with each other and with the key comparison reference valu of the comparison CCM.M-K5 to which the present comparison has been linked.